Isolation of potential Trichoderma spp. as biological control agents against rice blast Pathogen, Pyricularia oryzae / Siti Faridah Pauzi - Pauzi, Siti Faridah (Faculty of Plantation and Agrotechnology, 2018)
Rice is most important source to worldwide, especially in Malaysia in term of economic and as source of food. Moreover, rice is becoming sources of income for smallholder farmers. However, in this globalization the production of rice unable to fulfil the population demand because of the present of diseases. Rice blast is one of major diseases that causes by Pyricularia oryae and known as the most destruction disease that potential to cause 100% loss of yield under a favorable conditions. Although there have a lot of methods to control P. oryzae included use resistant varieties, applying fungicide and rotation farming unfortunately all of those method not long lasting. The aims of these study were to isolate Trichoderma spp. as a biological control agents against P. oryzae and to observe the inhibition of P. oryzae by Trichoderma spp. in vivo assays. Meanwhile, for species level of identify of Trichoderma spp. were done based on colony color and shape of conidia. There five of isolates of Trichoderma spp. which is TH1, TH2, TH3, TH4 and TM1. The potential of Trichoderma spp. to control P. oryzae was observed using dual culture technique. As biological control agent, isolates of Trichoderma spp. showed more than 50% growth inhibition of P. oryzae on the seven days of incubation in dual culture method and TM1 is the most effective among five isolates.